FIRST EURYPTERID FROM ITALY: A NEW SPECIES OFADELOPHTHALMUS (CHELICERATA: EURYPTERIDA) FROM THE UPPER CARBONIFEROUS OF THE CARNIC ALPS (FRIULI, NE ITALY) - JAMES C. LAMSDELL; LUCA SIMONETTO; PAUL A. SELDEN (Rivista Italiana di Paleontologia e Stratigrafia, 2013)
The first eurypterid known from Italy is described, as Adelophthalmus piussii n. sp. It comes from the Upper Carboniferous of the Carnic Alps (Friuli, NE Italy). Relationships with related species are discussed. Adelophthalmids are the commonest eurypterids of the late Palaeozoic, at which time the disparity of the order was waning. The new record enhances our knowledge of adelophthalmid distribution and diversity.